1998
DOI: 10.1007/s002239900488
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Modifications of the Extracellular Matrix Upon Calcification of Growth Plate Cartilage as Revealed by Quick-Freeze Deep Etching Technique

Abstract: The ultrastructural changes in cartilage matrix that occur during calcification have been examined in chick epiphyseal growth plate cartilage prepared by quick-frozen, deep-etched, and rotary shadowed replicas. The extracellular cartilage matrix contains a reticular network closely associated with an extensive network of collagen. The components of the reticular network, including thick and thin filaments, are attached directly to the cell membrane, matrix vesicle membrane, and collagen fibrils. This network, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…It may be speculated that an enzymatic mechanism removes the organic component, and that at the same time the residual inorganic backbone acquires further inorganic ions and 'matures', so turning into a hydroxyapatite crystal. This hypothesis is in agreement with the well-known fact that in cartilage the calcification process is characterized by changes in the organic matrix that chiefly imply the loss of acid proteoglycans [211][212][213][214][215][216][217][218][219][220][221][222][223][224]. In this connection, it is known that the calcification process is inhibited in vitro by proteoglycans and is increased by their degradation or removal [219,225], so that their controlled enzymatic breakdown could be considered a possible mechanism by which the calcification of growth plate cartilage might be allowed to advance in vivo [214].…”
Section: Crystal Ghosts and Calcificationsupporting
confidence: 90%
“…It may be speculated that an enzymatic mechanism removes the organic component, and that at the same time the residual inorganic backbone acquires further inorganic ions and 'matures', so turning into a hydroxyapatite crystal. This hypothesis is in agreement with the well-known fact that in cartilage the calcification process is characterized by changes in the organic matrix that chiefly imply the loss of acid proteoglycans [211][212][213][214][215][216][217][218][219][220][221][222][223][224]. In this connection, it is known that the calcification process is inhibited in vitro by proteoglycans and is increased by their degradation or removal [219,225], so that their controlled enzymatic breakdown could be considered a possible mechanism by which the calcification of growth plate cartilage might be allowed to advance in vivo [214].…”
Section: Crystal Ghosts and Calcificationsupporting
confidence: 90%
“…By combining biochemical with X-ray microprobe analyses, were able to confirm that the extracellular S content (per dry mass) is relatively constant at about 3.5% in the various zones of the epiphyseal cartilage, but falls to about 0.3% in the fully mineralized regions, indicating a loss of sulfurcontaining substances with calcification. Loss of glycosaminoglycans before or during cartilage calcification was confirmed by , Vittur et al (1979) and Mitchell et al (1982), and basic ultrastructural differences between uncalcified and calcified cartilage matrix were described by Akisaka et al (1998). A marked decrease in the size of granules, which are the form taken by cartilage protein-polysaccharides under the electron microscope (see Sect.…”
Section: Extracellular Matrix and Calcification: Acid Proteoglycansmentioning
confidence: 87%
“…The isolated crystals appeared under the electron microscope as thin, curved, rectangular platelets and, surprisingly, the needle-shaped crystals so often reported in intact calcified cartilage were not found; strangely enough, although the crystals had been deproteinated, 1-2% proteins were still present. Electron microscope investigations of the growth plate cartilage prepared by the quick-freeze, deep etching replica technique and conventional methods, showed that both needleand platelet-like crystals could be recognized in matrix vesicles (Akisaka et al 1998). Shitama (1979) found two different crystal shapes in an electron microscope study of calcified articular cartilage: slender, twisted, curved crystals, mainly located in the developing epiphysis, and short, needle-like, slightly curved crystals found in the calcified articular cartilage.…”
Section: Cartilagementioning
confidence: 99%
“…The territorial matrix encloses chondrons, while the interterritorial matrix lies between them. Given that collagen fibrils (the primary tensile mechanical component of cartilage) in the interterritorial matrix appear denser than the pericellular and territorial matrix (Akisaka et al, 1998), the shear-induced intercolumnar slip described in the current study is surprising. However, the interterritorial collagen network forms longitudinal septa oriented along the direction of growth, i.e.…”
Section: Discussionmentioning
confidence: 62%
“…Electron microscope imaging and histological investigations of growth plate ultrastructure have established that extracellular matrix is divided into three compartments: the pericellular matrix immediately surrounding each cell and the territorial and interterritorial matrices (Bonucci and Motta, 1990; Noonan et al, 2005; Akisaka et al, 1998). The territorial matrix encloses chondrons, while the interterritorial matrix lies between them.…”
Section: Discussionmentioning
confidence: 99%